Lebanon : Economic and Social Impact Assessment of the Syrian Conflict - World Bank (Washington, DC, 2014)
To provide a solid basis to define its needs and frame its priorities in terms of the specific assistance it seeks from the international community as well as to inform its own domestic policy response, the Government of Lebanon (GoL) requested the World Bank to lead an Economic and Social Impact Assessment (ESIA) of the Syrian conflict on Lebanon. Upon an official request from the Prime Minister of Lebanon, through a letter addressed to the World Bank dated July 25, 2013, this assessment has been conducted under the leadership of the World Bank, in collaboration with the United Nation (UN), the European Union (EU), and the International Monetary Fund (IMF). The outcome is the present report, of which the accuracy, quality and suitability for further dissemination is the responsibility of the World Bank, with input from the above mentioned key partners.